Otoritas Nilai Guru pada Sekolah Menengah di Era Digital - Ida Mariani Pasaribu; Osberth Sinaga; Wildansyah Lubis (Universitas Negeri Medan, 2025)
This research aims to analyse the transformation of teachers’ values of authority in the digital era, characterised by shifts in social interaction patterns and the spread of media culture. As technology and digital communities help students construct their own value horizons, teachers are no longer the sole sources of moral legitimacy. This study investigates how the Dialogic Value Authority Model can strengthen teachers’ moral legitimacy by focusing on five key dimensions: relationality, dialogic legitimacy, sustainability of moral dialogue, digital ethics, and the design of hybrid learning spaces. The findings indicate that teachers who internalise these five dimensions are able to restore students’ moral trust through equitable relationships and reflective communication. Practically, the study recommends reforming teacher training policies toward digital moral literacy and establishing digital ethics policies in schools. Theoretically, it integrates the concept of reflective authority into the philosophy of educational management, positioning teachers as moral facilitators and value managers. In this age of computers and the internet, the proposed model offers a new approach to managing education that is moral, inclusive, and contextually responsive.